Understanding the Old Testament - Anderson, Bernhard W. (Englewood Cliffs, NJ Prentice Hall, 1986)
Includes bibliographical references and index.
Keywords: Bible. O.T. -- history of biblical events; Jews -- history -- to 70 A.D.